Frequency-domain information for active portfolio management - Gonçalo Faria; Fabio Verona (Bank of Finland, 2020)
We assess the benefits of using frequency-domain information for active portfolio management. To do so, we forecast the bond risk premium and equity risk premium using a methodology that isolates frequencies (of the predictors) with the highest predictive power. The resulting forecasts are more accurate than those of traditional forecasting methods for both asset classes. When used in the context of active portfolio man- agement, the forecasts based on frequency-domain information lead to better portfolio performances than when using the original time series of the predictors. It produces higher information ratio (0.57 vs 0.45), higher CER gains (1.12% vs 0.81%), and lower maximum drawdown (19.1% vs 19.6%).
URN:NBN:fi:bof-202001091008
Keywords: C58; G11; G17; 330; equity risk premium; bond risk premium; predictability; multiresolutionanalysis; active portfolio management